Os conceitos da Justiça em Aristóteles: a construção dos conceitos de Justiça apresentado no quinto livro da Ética à Nicômaco - Vítor Hugo Diniz Oliveira (2018)
Dissertation presented as an requirement for the obtainment of the degree of Master by the Faculdade de Direito da Universidade Federal de Minas Gerais. This work had as its object the concepts of Justice described by the classical philosopher Aristotle through a conceptual construction that had as its base the concepts of Man, Act, Potency, Finality and Virtue. The author occupied himself primarily on the working with the base concepts as to creat a chain of reasoning that might take to the concepts of Justice on a cohese and complete manner; therefore the first chapters are deicated to describing the Man, Act, Potency, Finality and Virtue. Moving on, the text will work with the greater Justice, in other words, Justice as a Complete Virtue especifying what is this conceptualization and what is connected with it, such as habituality and routine of the just act, the difference between just and unjust acts, and finally the separation between Justice and Injustice. As this part is finished this work will focus on the minor justices, those being: Legal Justice, Distributive Justice, Commutative Justice, and some aspects Aristole judges necessary to work with regarding Justice and commerce, a Comercial Justice. By the end os this dissertation it is hoped to conclude that it was possible to presente the aristotelic vision of Justice in a cohese, complet and clear manner, allowing the readers a less sectarist, and, therefore, more organic vision of the immense contribution of Aristotle to the formation of the western juridical-philosophical tradition.